2020
DOI: 10.1111/1365-2435.13510
|View full text |Cite
|
Sign up to set email alerts
|

Plant roots stimulate the decomposition of complex, but not simple, soil carbon

Abstract: Roots release carbon into soil and can alleviate energy limitation of microbial organic matter decomposition. We know little about the effects of roots on microbial decomposition of different organic matter substrates, despite the importance for soil carbon stocks and turnover. Through implementing root–microbe interactions, the Carbon, Organisms, Rhizosphere and Protection in the Soil Environment (CORPSE) model was previously shown to represent dynamics of total soil carbon in temperate forest field experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 49 publications
(73 reference statements)
2
16
0
Order By: Relevance
“…1a) and follows from the idea that the decay of cellulose, hemicellulose, and lignin requires the production and excretion of extracellular enzymes that are quite energy demanding (Deacon 2006). This also agrees with recent observations that labile root exudates stimulate the decomposition of complex, but not simple, soil carbon in the rhizosphere (Moore et al 2019). Based upon the values of the path coefficients, an increase in the rate of decomposition of the water‐soluble fraction ( k S ) increases the decomposition rate of the hemicellulose, cellulose, and lignin fractions about equally.…”
Section: Discussionsupporting
confidence: 93%
“…1a) and follows from the idea that the decay of cellulose, hemicellulose, and lignin requires the production and excretion of extracellular enzymes that are quite energy demanding (Deacon 2006). This also agrees with recent observations that labile root exudates stimulate the decomposition of complex, but not simple, soil carbon in the rhizosphere (Moore et al 2019). Based upon the values of the path coefficients, an increase in the rate of decomposition of the water‐soluble fraction ( k S ) increases the decomposition rate of the hemicellulose, cellulose, and lignin fractions about equally.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, soil C storage is also largely dependent on the C input (Riggs et al, 2015), thus the higher ne root biomass and production under TFR treatment may also facilitate soil C sequestration. However, recent studies have demonstrated that plant roots or belowground C allocation can drive the soil SOM decomposition (Moore et al, 2020;Street et al, 2020), indicating that the ne roots had a dual role in regulating soil C storage (Dijkstra et al, 2020). Our results suggest that how prolonged drought will ultimately in uence SR, and therefore soil C storage, will depend not only on soil microorganisms but also on plant belowground C allocation.…”
Section: Relative Contribution Of Ar and Hr To Srmentioning
confidence: 63%
“…However, this relationship supports the positive impact of residue retention on N-supply to the total plant-available N pool. Moore et al (2020) showed that in soil environments dominated with leaf litter, even small amounts of root C inputs could significantly stimulate microbial decomposition of complex C compounds. Surey et al (2020) also demonstrated the importance of…”
Section: Som Mineralisation and Nitrificationmentioning
confidence: 99%